Pengaruh Electronic Word Of Mouth Dan Initial Brand Trust Terhadap Consumers Purchase Intention (Universitas Gresik, 2023)
The purpose of this study was to analyze the effect of Electronic Word of Mouth Positive Valence, Electronic Word of Mouth Negative Valence and Initial brand trust on Consumers Purchase Intention on the Erigo brand. Data was obtained by distributing online questionnaires to Erigo clothing users who bought online in the past year. The sample used in this study was 178 respondents. The sampling method used in this research is purposive sampling. The data analysis method used in this study is to analyze the influence between the variables that are owned using the Multiple Linear Regression method with the help of SPSS 25 software. The results of this study conclude that Electronic Word of Mouth Positive Valence has a positive effect on Initial brand trust, Electronic Word of Mouth Negative Valence has no positive effect on Initial brand trust, Electronic Word of Mouth Positive Valence has a positive effect on Consumers Purchase Intention, Electronic Word of Mouth Negative Valence has no positive effect on Consumers Purchase Intention, Initial brand trust has a positive effect on Consumers Purchase Intention.